DIAGNOSTIC VALUE OF SEROLOGICAL MARKERS OF RHEUMATOID ARTHRITIS - Aleksei Leonidovich Maslaynski; S V Lapin; A V Mazing; T V Bulgakova; N M Lazareva; M D Cheshuina; P A Oleinick; E P Ilivanova; A A Totolyan; V I Mazurov (Научно-практическая ревматология)
Rheumatoid arthritis (RA) is a classic autoimmune disease associated with the production of wide range of autoantibodies, and their detection has diagnostic and prognostic implication. The objective of this study was to estimate the diagnostic value of antibodies against modified citrullinated vimentin (AMCV) and nuclear antigen RA33 of the IgA rheumatoid factor (RF) versus the value of routinely used profile of autoantibodies in diagnostic work-up of RA. Material and methods. 253 patients with RA prehistory of varying duration were included into the study group. The control group was comprised of 92 patients, including patients with seronegative spondyloarthropathies and diffuse connective tissue diseases, as well as sex and age matched healthy controls. Serum levels of IgM and IgA RF, antibodies against cyclic citrullinated peptide (ACCP), ACMV, anti-keratin antibodies (AKA), antibodies against RA33 antigen (ARA33) and antinuclear factor (ANF) were measured in all patients and controls. Results and discussion. Diagnostic sensitivity of AMCV equaled 78%, ACCP — 77%, IgM RF — 71%, IgA RF — 43%, AKA — 43%, ARA33 — 31% and ANF — 31%. All anti-citrullinic antibodies (AKA, ACCP, ACMV) were significantly more commonly associated with IgM RF. Among RF and ACCP seronegative patients ACMV were found in 24% cases with 20 IU/Ml detection threshold, and in 21% — with 30 IU/Ml, allowing to increase diagnostic specificity of the test up to 91% with the increment of diagnostic threshold. Incidence of ARA33 was not significantly different among the RF and ACCP positive or negative subgroups, thus making ARA33 an independent RA marker. Specificity of this marker was 87,9%, thus making it inferior to RF and ACCP by a composite of diagnostic characteristics. Conclusions. Integrated measurement of ACMV and ARA33 is a rational approach at the second stage of serologic testing work-up in suspected cases of RA onset, when initial RF and ACCP tests were negative.